12x+3y=9

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 12x from both sides of the equation.

3y=9-12x

Divide each term by 3 and simplify.

Divide each term in 3y=9-12x by 3.

3y3=93+-12×3

Cancel the common factor of 3.

Cancel the common factor.

3y3=93+-12×3

Divide y by 1.

y=93+-12×3

y=93+-12×3

Simplify 93+-12×3.

Simplify each term.

Divide 9 by 3.

y=3+-12×3

Cancel the common factor of -12 and 3.

Factor 3 out of -12x.

y=3+3(-4x)3

Cancel the common factors.

Factor 3 out of 3.

y=3+3(-4x)3(1)

Cancel the common factor.

y=3+3(-4x)3⋅1

Rewrite the expression.

y=3+-4×1

Divide -4x by 1.

y=3-4x

y=3-4x

y=3-4x

y=3-4x

Reorder 3 and -4x.

y=-4x+3

y=-4x+3

y=-4x+3

y=-4x+3

Using the slope-intercept form, the slope is -4.

m=-4

Find the Slope 12x+3y=9